DESIGNING A BRIGHT FUTURE: HOLISTIC EDUCATION AS THE KEY TO CHARACTER AND COMPETENCE BUILDING - Bai Rohimah; Taswiyah Taswiyah; Suja'i Saleh (Adisam Publisher, 2025)
A holistic approach in modern education is essential as it aims to prepare individuals for the challenges of the 21st century. Holistic education seeks to integrate the development of students' academic, emotional, social and spiritual aspects, with the aim of creating balanced and adaptive individuals. In fact, the holistic approach in education is considered to support the formation of strong character and diverse competencies, through interactive and collaborative learning methods that involve the active involvement of the community, including family and society. As such, holistic education focuses not only on academic outcomes but also on building whole people who are ready to contribute positively and effectively in society and the future world of work.